SISTEM INFORMASI PEMESANAN MAKANAN ONLINE - Moniqah Febbyanti Siregar; Ryanalea Ananda Adithia; Ratu Azizzah; Iin Ernawati (Jurnal Riset Sistem Informasi, 2025)
The consumption pattern of society has been changed by advances in information and communication technology, especially in terms of online food and beverage ordering. In order for the process to run efficiently and reliably, an ideal database design is needed to support this system. However, previous studies have focused more on the appearance of the interface and application functions, while database design has not been studied thoroughly. This study uses the Life Cycle of Database System Development (DBSDLC) methodology, which includes the planning stage, literature research, and database design. Starting by creating a conceptual ERD, finding primary and potential keys, and then developing a logical model through validation and optimization of the structure. The results of the study produce a database model with main entities such as customers, orders, menus, payments, addresses, vouchers, transactions, baskets, and admins. All entities are connected to the conceptual ERD with clear and structured relationships. Payment types, menu variations, and order items are some of the system complexities that can be handled by this model. This construction plays an important role in creating an effective online food ordering system.